2020
DOI: 10.3390/app10072624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Earthworms’ Potential for Remediating Soils Contaminated with Olive Mill Waste Sediments

Abstract: The olive-oil industry generates large amounts of residues that, in the past, were accumulated in evaporating ponds in many Mediterranean countries. Currently, these open-air ponds pose a serious environmental hazard because of toxic chemicals that concentrate in their sediments. Bioremediation of olive mill waste (OMW) sediments has emerged as a viable option for managing this environmentally problematic residue. Here, we postulate that inoculation of an OMW-soil mixture with earthworms may be a complementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Our study showed that the sewage sludge induces changes in the activity of crucial enzymes of earthworms responsible for the metabolism of the energy, neurotransmission, and oxidation systems. The dosedependent response was observed by increasing the concentration of sewage sludge enzyme inhibition (Sanchez-Hernandez et al, 2020). In the case of sewage sludge, acid phosphatase activity was affected by sewage sludge followed by biochar and at the same concentrations of these amendments also caused inhibition of acetylcholinesterase activity within earthworms.…”
Section: Discussionmentioning
confidence: 95%
“…Our study showed that the sewage sludge induces changes in the activity of crucial enzymes of earthworms responsible for the metabolism of the energy, neurotransmission, and oxidation systems. The dosedependent response was observed by increasing the concentration of sewage sludge enzyme inhibition (Sanchez-Hernandez et al, 2020). In the case of sewage sludge, acid phosphatase activity was affected by sewage sludge followed by biochar and at the same concentrations of these amendments also caused inhibition of acetylcholinesterase activity within earthworms.…”
Section: Discussionmentioning
confidence: 95%